Study on soliton pulse and its characteristics for fiber optic communication - Bhuvaneshwari, M.; ShaziaHasan, Dr.; Abdul Razak, Dr. (International Journal of Engineering and Technology, 2018)
From time immemorial communication is an essential need for human beings. Communication happens through the channel. Among many channels for communication, Fiber is a vital wired channel that has infinite bandwidth and high noise immunity against electromagnetic interference. The phenomenon of dispersion is the major problem for high bit rate and long-haul optical communication systems. An easy solution to this problem is optical Solitons - Pulses that preserve their shape over long distances. Soliton based optical communication systems establish over distances of several thousands of kilometers with considerable information carrying capacity by using optical amplifiers.Â Â